Development of a java library to solve the school bus routing problem - Ochoa, Alberto (Springer, 2020)
Since transport is an inalienable right for students in many countries of the world, the problem of school bus routing problem (SBRP) arises, where some students spend a lot of time on these routes. Several restrictions are presented, such as the time of arrival at class and the number of students who can travel on a bus. These restrictions are considered to make the best optimization of routes, with the minimum number of buses needed to move all students, whether from a school or a school district. The school bus routing problem can be modeled computationally, and there are several proposals to solve it, in which some of these were not developed as a program; they remained only in a theoretical approach (as algorithms, pseudocode). There are some proposals in which, if developed as code, such programs are focused on solving the problem in their environment, which makes them difficult to reuse for some other case of school bus routing problem.